2018
DOI: 10.21161/mjm.106617
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic activity of Streptomyces thermocarboxydus to Fusarium oxysporum: The cause of leaf rot disease on Aloe Vera (Aloe barbadensis Mill.) in Bali, Indonesia

Abstract: Aims: Aloe vera (Aloe barbadensis Miller) has been cultured in Bali, Indonesia since 2006. Its cultivation area is 170 ha including 5 regencies i.e. Buleleng, Karangasem, Bangli, Badung and Gianyar. This study was conducted to isolate and identify the Streptomyces sp. that potentially can be used to inhibit the growth of F. oxysporum and control the leaf rot disease on aloe vera with and to study the structural responses of F. oxysporum to the treatment of Streptomyces culture filtrate. Methodology and results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…These results are relatively consistent with previous studies showing the effect of antagonistic microorganisms in reducing the incidence of different Fusarium diseases [5, 16-19, 30, 46-49]. They act against pathogens by synthesizing antimicrobial secondary metabolites [13,15,20,26,28,31], induce systemic resistant in plants [7,8,16,17,26,27], inhibit the growth of pathogens, and suppress disease incidence and severity [5, 8-11, 13, 14, 16, 18, 19, 21-24, 30, 32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are relatively consistent with previous studies showing the effect of antagonistic microorganisms in reducing the incidence of different Fusarium diseases [5, 16-19, 30, 46-49]. They act against pathogens by synthesizing antimicrobial secondary metabolites [13,15,20,26,28,31], induce systemic resistant in plants [7,8,16,17,26,27], inhibit the growth of pathogens, and suppress disease incidence and severity [5, 8-11, 13, 14, 16, 18, 19, 21-24, 30, 32].…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports indicated that different antagonistic microorganism inhibit the growth of Fusarium spp. that are the causal pathogens of different diseases [7,8,16,17]. The introduction of MICROTECH-1(NL) into culture medium significantly suppressed the mycelial growth of FP isolates by 70.38-72.04% higher than that from other tested bio-products (52.84% for Ketomium to 67.30% for SH-BV1) (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Kedua larutan dihomogenkan dan didiamkan selama 24 jam sampai fase air dan fase n-butanol terpisah. Fase n-butanol dievaporasi dengan mesin rotary evaporator dengan suhu 40°C hingga didapatkan sebanyak ± 5 mL filtrat yang dianggap sebagai konsentasi 100% (Kawuri et al, 2018). Filtrat yang didapat adalah filtrat kasar dari Streptomyces sp.5 dan hasil tersebut selanjutnya diuji secara in vitro terhadap C. acutatum dengan metode sumur difusi.…”
Section: Re-isolasi Jamur C Acutatumunclassified
“…2012), maize (Bressan and Figueiredo 2008), aloevera (Kawuri et al . 2018), cotton (Zhang et al . 2018), asparagus (Elson et al .…”
Section: Introductionmentioning
confidence: 99%